Estudo da passivação dos aços CA-50 e ASTM 1035 9100 submetidos a soluções alcalinas simuladas de cimentos álcali-ativados sob carbonatação - Krein, Laércio Antonio (Universidade do Vale do Rio dos Sinos, 2025)
Concrete is widely used in construction due to its strength; however, its production consumes large amounts of energy and emits significant quantities of carbon dioxide. With population growth and the increasing demand for infrastructure, the environmental impacts of this process become even more critical. In this context, alkaliactivated materials have gained attention for their ability to reduce emissions and enable the reuse of industrial residues, although further research is still required regarding their protective performance for embedded steel reinforcement. Additionally, since concrete is a highly alkaline medium, the potential for carbon dioxide capture by concrete structures can be explored. However, alternatives to CA-50 steel, widely used in reinforced concrete structures in Brazil, must also be considered. In this context, corrosion-resistant ASTM A1035 9%Cr (MMFX) steel emerges as a promising option. Thus, the present study aimed to evaluate the protective capacity of simulated alkaliactivated and Portland cement solutions on CA-50 and MMFX steel, both in their original pH and during the pH reduction of the solutions. Steel samples were exposed to the testing environment in their as-produced state, without surface treatment to remove the oxide layer commonly present on rebars. Moreover, the passive film was formed in different simulated solutions based on alkali-activated cements (with pH values and ionic concentrations much higher than those of Portland cement, used as a reference). These same samples remained in contact with the solutions throughout the carbonation process (with pH ranging from 14.57 to 8), ensuring that the components formed at higher pH levels continued to interact with the medium on the sample surface at lower pH levels. After conducting tests such as corrosion potential, polarization resistance, Tafel, cyclic voltammetry, and electrochemical impedance spectroscopy, it was observed that simulated alkali-activated solutions with excessively high pH levels, while forming passive films on CA-50 steel, did not form protective films on MMFX steel. This behavior is likely due to the high solubility of chromium hydroxides in these environments. However, as pH decreased due to carbonation, alkali-activated solutions began to provide protection to the steels. Notably, even at pH levels below 11, MMFX steel reinforcements remained passivated, indicating the potential for stimulating carbonation in reinforced concrete structures to capture and store CO₂ within the cement matrix. Nonetheless, despite these promising Therefore, future research should also include testing on physical specimens to validate these results.
Keywords: Carbonatação; Álcali-ativados; Concreto; Corrosão; CO2; Carbonation; Alkali-activated; Concrete; Corrosion; ACCNPQ::Engenharias::Engenharia Civil